Exploring Publication Trends, Geographic Contributions, and Research Collaborations in Virtual Labs for Physics Learning: A Systematic Literature Review - Hamdani Hamdani; Reni Marlina; Chokchai Yuenyong (FKIP Universitas Lampung, 2026)
This study aims to review and synthesize research trends on the application of virtual laboratories in physics education published between 2015 and 2025. It focuses on identifying dominant themes, research directions, and emerging opportunities in integrating digital technologies into physics learning. A systematic literature review approach was employed by selecting articles from Scopus-indexed journals and conference proceedings. Relevant studies were identified using keywords related to virtual laboratories, physics education, and digital learning. The selected articles were analyzed using bibliometric and thematic analysis to map publication trends, author contributions, and keyword co-occurrence patterns. The results indicate a significant increase in publications on virtual laboratories, particularly during and after the COVID-19 pandemic. Authors from Indonesia emerged as the most prolific contributors in this field. The dominant themes in virtual laboratory research were closely associated with distance learning and digital technology, reflecting the growing reliance on online and hybrid learning environments. Additionally, virtual lab studies were frequently linked to broader educational themes, including e-learning, curriculum development, and STEM education. Despite these developments, the integration of advanced technologies, such as artificial intelligence, remains limited and represents a strong area of potential for future exploration. Virtual laboratories have become an essential component of physics education, supporting flexible and interactive learning environments. However, current research remains largely focused on basic digital integration rather than on intelligent or adaptive systems. Future studies are recommended to explore the incorporation of artificial intelligence and more advanced pedagogical frameworks to enhance the effectiveness and personalization of virtual lab experiences. Keywords: virtual lab, systematic literature review.